Psychoeducational intervention models in physical activity programs for health: a systematic literature review - Mulyadi, Rekyan Woro Mulaksito; Nugroho, Wisnu; Widyastuti, Candra; Wibowo, Moch. Septian Resi; Utomo, Suryo; Nugroho, Agung Wahyu (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This systematic literature review examines psychoeducational intervention models integrated into physical activity programs and their relevance to health-related outcomes. The review synthesizes evidence from multidisciplinary studies addressing psychological, behavioral, and physical dimensions of health across diverse populations. Findings indicate that psychoeducational components, including health education, self-efficacy enhancement, motivational support, and reflective practices, strengthen the effectiveness of physical activity interventions by promoting sustained behavioral change and psychological well-being. These models demonstrate consistent benefits in improving mental health indicators, adherence to physical activity, and overall quality of life in both clinical and non-clinical settings. The review also highlights the importance of program structure, participant engagement, and contextual adaptation in determining intervention success. Furthermore, the growing integration of digital health technologies expands opportunities for scalable and personalized psychoeducational delivery within physical activity programs. Psychoeducational intervention models offer a comprehensive framework for advancing health promotion strategies in the field of physical activity and sports health. Future development should prioritize holistic, evidence-based, and context-sensitive approaches to maximize long-term health outcomes.